The black male educator guide to thriving - Sandles. David (Emerald Publishing Limited, 2025)
The Black Male Educator Guide to Thriving aims to advise Black male educators in various areas of their professional responsibilities. While anti-Blackness is rampant, Black educators need support and mentorship to develop in their educational bearing. By extension, this book is also intended to support Black male educators and those who support them in the immersion of effective practices to erode environments of the antiracism that plague them. Full of practical tips, case studies, and real-world examples and offering best practices derived from cutting-edge research, the book is a versatile resource designed to educate, inspire, and entertain. It significantly advances the field by exploring previously unrecognized or infrequently considered topics through innovative research questions, the inclusion of diverse perspectives, and a focus on contemporary issues. Whether readers are seeking to gain knowledge, apply practical advice, find personal motivation, or engage in perspective-taking or community discussions, this book provides the tools and content to meet those needs. By exploring its pages, readers can expect to enhance their understanding, improve their skills, and find enjoyment and inspiration.
Includes index.
Keywords: African American teachers.; Education -- Teaching -- Methods & Strategies.; Teaching skills and techniques.; elektronické knihy; electronic books